Bivalirudin More Beneficial than Heparin in Patients with AMI Undergoing PCI: The BRIGHT Trial - Vinall, Maria (MD Conference Express, 2014)
Although 2 studies [Stone GW et al. N Engl J Med. 2008; Steg PG et al. N Engl J Med. 2013] have documented the superiority of bivalirudin over heparin in patients with acute myocardial infarction (AMI) undergoing primary percutaneous coronary intervention (PCI), a third study showed heparin to be associated with fewer major adverse ischemic events with no increase in bleeding [Shahzad A et al. Lancet. 2014]. This article presents the results of the Bivalirudin in Acute Myocardial Infarction vs Glycoprotein IIb/IIIa and Heparin trial [BRIGHT; NCT01696110] in which bivalirudin monotherapy led to better 30-day and 1-year outcomes in these patients compared with heparin monotherapy or heparin plus tirofiban.